OPTIMIZATION OF PREVENTIVE MAINTENANCE AND REPLACEMENT INTERVAL OF CRITICAL COMPONENTS IN THE CUMMINS KTA 38D DIESEL GENERATOR - Wakijo Wakijo; Suparno Suparno; Eko Krisdiono; Anton Nugroho (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2022)
The Cummins KTA 38D brand diesel generator is a ship's power generation equipment owned by a supplier to warship electrical needs both at base or in operation. Based on damage report data from 2016 - 2022, the percentage of diesel generator damage reached 38.5% of the total damage to all ship equipment. The results of the analysis using the FTA method cause the failure of the diesel generator to be caused by one of the failure factors in the supporting sub-systems,both from the electrical sub-system, fuel sub-system, air sub-system, fresh water sub-system, seawater sub-system, the lubricant sub-system and the control sub-system were damaged. Calculation using FMECA, there are five critical components based on the RPN value with a